Size reduction-induced properties modifications of antiferromagnetic dielectric nanocrystalline Ba2NiMO6 (M = W, Te) double perovskites. Issue 1 (21st October 2020) - Bijelić, Jelena; Tatar, Dalibor; Sahu, Manisha; Jagličić, Zvonko; Djerdj, Igor
Abstract: The main objective of this work was to synthesize phase pure double perovskites Ba2 NiTeO6 (BNTO) and Ba2 NiWO6 (BNWO) in nanocrystalline form and to reveal the impact of nanocrystallinity on their magnetic and dielectric properties. The studied double perovskites were synthesized in nanocrystalline form by employing a citrate sol-gel route. A detailed investigation of their structure and properties using X-ray powder diffraction, scanning electron microscopy, Raman spectroscopy technique, energy-dispersive X-ray spectroscopy, SQUID magnetometry and electrical measurements is carefully described. Rietveld refinement of X-ray powder diffraction patterns revealed phase purity of both compounds: BNTO is trigonal ( R -3 m ) while BNWO is cubic ( Fm -3 m ). Raman spectroscopy studies reveal optical phonons that correspond to vibrations of Te 6+ /W 6+ O6 octahedra, while scanning electron microscopy images show irregular plate-like nanocrystals. Magnetic property measurements speak in favor of antiferromagnetic order but, in both compounds, size reduction affected their properties. BNTO has Néel temperature (TN ) of 10.3 K which is higher than previously reported for its bulk form. Magnetic ground state of BNWO can be explained as canted antiferromagnetism with TN = 48.2 K. Room temperature measurements of dielectric constants at various frequencies suggest that these materials are high-κ dielectrics with low dielectric loss. The Nyquist plot reveals depressed a semicircle arc typical for non-Debye type of relaxation phenomena for BNWO ceramic, whereas for BNTO ceramic an almost straight line of Zʹʹ versus Z' has been observed, indicating its high insulating behavior. To conclude, size-dependent properties of studied double perovskites are discussed, introducing a possibility for implementation in electronic devices.